Kompetensi Kemahiran Berbahasa Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Riau - Sukenti, Desi; Tambak, Syahraini; Fatmawati, Fatmawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
This study aimed to analyze the literacy competencies of students' language proficiency in the aspects of listening, responding to the rules, reading and writing. Literacy competence is a competency that must be considered by educators in honing language proficiency which is an important issue, especially in the development of language skills in students. This research used a quantitative-descriptive method. The data obtained from this study were the results of the Indonesian language proficiency test (UKBI) of students in the Indonesian Language and Literature Education study program. The population used in this study were students of the Indonesian Language and Literature Education study program, while the sample who had taken the UKBI test was 24 students. The results of this study indicated that the students' language proficiency literacy competence in the listening aspect obtains an average of 538, responds to the average rule of 464, reads an average of 519, and writes an average of 596. The overall average of language proficiency literacy competencies was 529. Twenty-five was in the middle-ranking, indicating that students have adequate proficiency in communicating using Indonesian, both oral and written. With these skills, the student concerned can understand factual information, properly capture and re-reveal information.